Analisis Pengalaman Pengguna pada Sistem V-Soft Akuntansi Menggunakan Metode User Experience Questionnaire - I Wayan Aditya Wiguna; Dede Desnantha Putra; Ade Surya Indrawan; I Made Agus Oka Gunawan; Gede Indrawan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
The V-Soft application offers module integration and inventory management through a user-friendly interface. However, with technological advancements, users expect a system that is not only accurate and efficient but also easy to use and enjoyable. This study examines six user experience dimensions: attractiveness, clarity, efficiency, dependability, stimulation, and novelty, based on data collected from 104 users through a questionnaire comprising 26 items. The analysis results indicate that the dimensions of attractiveness (4.88) and novelty (5.03) received positive scores, suggesting that users find the application appealing and innovative, particularly in the financial reporting features. The stimulation dimension also recorded a high score (4.80), indicating that the application's features provide motivation and engagement for users. However, the efficiency (3.27) and dependability (3.00) dimensions showed low scores, reflecting challenges in completing tasks quickly and accurately, as well as a lack of user motivation to use the application consistently. Meanwhile, the clarity dimension (4.10) was moderate, suggesting that the application's interface still requires improvement. In conclusion, the V-Soft Accounting application is considered attractive and innovative, especially in terms of its attractiveness and novelty.   Keywords— User experience, V-Soft Accounting, User Experience Questionnaire, user-friendly.